Learner-generated drawings in physics education - Lehtinen, Antti (2013)
Different kinds of visual representations, such as graphs and drawings are important in education but especially in science education. Little attention is paid especially to drawings. Students are required to examine drawings and assimilate the information conveyed by them but not much attention is paid to the students’ own drawings. Arguments can be made for the importance of learner-generated drawings in science education. The subject of this thesis is the use of learner-generated drawings in physics education. A study was conducted to study the use of learner-generated drawings as a tool for meaning-making. The study involved 36 upper secondary school students who were given a drawing assignment about the kinetic theory of gases. The students also had to solve few assignments by drawing the answer. The students drew in small groups and the drawing process and the students’ talk were recorded using iPads. The quality of the students’ talk was analysed. The effect of guidance in the drawing process was also studied. Half of the groups received guidance by comparing their own drawing to another drawing about the same subject. The students used drawings and talk as psychological tools that helped them process their internal models and to visualize and verbalize them. Many of the drawings produced resembled traditional text books drawings. It seems that the most of the students had learned the conventions of drawing the kinetic theory of gases. Statistical methods show that students who received guidance drew more accurately than the control group. The students’ talk was generally cumulative and uncritical. Seldom did the students open up the conversation and look for alternative solutions. iPads performed well as research equipment. They offer some benefits over traditional research equipment. There is a need for specially coded applications for education research for tablet computers. At the end of this thesis ideas for future research are presented.